Improved strength of peat soil by using kaolin and quicklime stabilizer - Hazrim, Abdul Karim (2016)
Due to tropical climate and topographical conditions, peat soil or organic soil is abundant in Malaysia. Peat soil is also known as problematic soil due to low in shear strength and high compressibility. This research focus on shear strength and the objective was to find out the effectiveness of kaolin and quicklime as stabilizer to enhance the shear strength of peat soil. The study area of this research was at Indera Sempurna, Pekan, Pahang while the kaolin and quicklime used were S300 and plaster mix A1. To achieve the objective, test specimens of both untreated and stabilized peats were tested in laboratory in order to evaluate its unconfined compressive strength. Peat soil that passes through 2 mm sieve size was used to mix with kaolin and quicklime. Amount of stabilizers used consist of 2%, 5% and 8% for kaolin and 3%, 7% and 10% for quicklime. The correlation between the amount of stabilizer and shear strength of peat soil was determined using the kaolin and quicklime. All samples cured for 7, 14 and 28 days respectively. The expectation from this research was to increase the shear strength of peat by adding kaolin and quicklime as stabilizer.